Motivation factors attributed to engaging in online studies amongst public university students - Balan Rathakrishnan; Soon Singh Bikar Singh; Mohd Fahmi Ghazali; Azizi Yahaya; Noor Hassline Mohammed; Mohammad Rahim Kamaluddin (Springer, Cham, 2021)
This research study investigated the engagement and motivation levels amongst young adults of different genders from a public university, with regards to engaging in online studies. The data was obtained through the use of a questionnaire, where a total of 190 public university students in Sabah participated. This study revealed three major outcomes attributed to the motivation levels to engage in online studies. Firstly, there were no significant differences in online learning factors between both male and female students. Secondly, there was a significant relationship between the motivation and engagement factors attributed to online learning amongst the young adults in the public university. Thirdly, it was found that motivation helps predict the engagement outcomes in online learning amongst these young adults. This research contributed to the understanding of online studies, and how it helps students be well prepared in future digital learning environments.